The Mediating Role of Tourist Satisfaction in the Relationship Between Destination Image and Word-of-Mouth Communication - Khadka, Bhim Bahadur (Journal of Nepalese Management and Research, 2025)
Satisfied tourists generate positive word-of-mouth, shaping destination image and influencing travel decisions. Positive WOM enhances reputation, attracts visitors, and promotes repeat travel, whereas negative WOM harms perceptions. The fact that destination image (DI), tourist satisfaction (TS), and word-of-mouth (WOM) all affect each other shows how important it is for tourism stakeholders to address these issues in a planned way to make destinations more competitive and long-lasting. This study examines the influence of DI and TS on PWOM communication within Nepal’s tourism sector. Acknowledging PWOM’s pivotal role in travel decision-making, the study investigates the direct and indirect relationship through which DI affects PWOM, with TS as a mediator. Using a structured questionnaire, the study collected data from 450 tourists visiting Shey Phoksundo Lake, Nepal, through purposive sampling. After excluding incomplete responses and multivariate outliers, 354 valid cases remained. Structural equation modelling with maximum likelihood estimation was applied to examine the hypothesized direct and indirect relationships. The results confirm that DI has a positive and significant direct influence on TS, and TS, in turn, has a positive and significant influence on PWOM communication. In addition, the results demonstrate that TS fully mediates the relationship between DI and PWOM, revealing no direct DI-PWOM relationship. These findings underscore the necessity of enhancing destination attractiveness and prioritizing tourist satisfaction to amplify PWOM and foster destination competitiveness. The study offers practical implications for Nepalese tourism stakeholders, emphasizing strategies to improve infrastructure, service quality, and emotional engagement to drive sustainable tourism growth.